Does an inverted pendulum model represent the gait of individuals with unilateral transfemoral amputation while walking over level ground?. (April 2019) - Strutzenberger, Gerda; Alexander, Nathalie; De Asha, Alan; Schwameder, Hermann; Barnett, Cleveland Thomas
Background: An inverted pendulum model represents the mechanical function of able-bodied individuals walking accurately, with centre of mass height and forward velocity data plotting as sinusoidal curves, 180° out of phase. Objectives: This study investigated whether the inverted pendulum model represented level gait in individuals with a unilateral transfemoral amputation. Study Design: Controlled trial. Methods: Kinematic and kinetic data from 10 individuals with unilateral transfemoral amputation and 15 able-bodied participants were recorded during level walking. Results: During level walking, the inverted pendulum model described able-bodied gait well throughout the gait cycle, with median relative time shifts between centre of mass height and velocity maxima and minima between 1.2% and 1.8% of gait cycle. In the group with unilateral transfemoral amputation, the relative time shift was significantly increased during the prosthetic-limb initial double-limb support phase by 6.3%. Conclusion: The gait of individuals with unilateral transfemoral amputation shows deviation from a synchronous inverted pendulum model during prosthetic-limb stance. The reported divergence may help explain such individuals' increased metabolic cost of gait. Temporal divergence of inverted pendulum behaviour could potentially be utilised as a tool to assess the efficacy of prosthetic device prescription. Clinical relevance: The size of the relative time shifts between centre of mass height and velocity maxima and minima could potentially be used as a tool to quantify the efficacy of innovative prosthetic device design features aimed at reducing the metabolic cost of walking and improving gait efficiency in individuals with amputation.